HOW GOVERNMENT PUBLIC RELATIONS SHOULD EXECUTE SOCIAL ENGINEERING: A LITERATURE REVIEW ABOUT HOW INDONESIA GOVERNMENT’S PUBLIC RELATIONS EXECUTE SOCIAL ENGINEERING ON MULTI PERSPECTIVE - Sugeng, Ayu Sulistya Putri; Jufri , Devi; Mondigir , Anastasia Ade Febriany (DAS Institute, 2023)
This study aims to describe how the Public Relations of the Indonesian government carries out social engineering in dealing with the COVID-19 pandemic crisis from various perspectives, including the perspectives of government, society, and academics. In facing this crisis as a global issue, the government needs to be transparent and use various types of internet-based media to increase public trust and the effectiveness of crisis management. The government must also overcome the digital divide which is one of the main problems in spreading the social engineering agenda to the public. This study will use a literature review to describe how the Indonesian government's Public Relations carried out their main task in dealing with this crisis as well as the expectations and views of the government and society regarding the social engineering that was carried out. With data from various perspectives, the author hopes to provide broad insights to readers through this paper.